Foulant Characteristics Comparison in Recycling Cooling Water System Makeup by Municipal Reclaimed Water and Surface Water in Power Plant. (29th March 2015) - Ping, Xu; Jing, Wang; Yajun, Zhang; Jie, Wang; Shuai, Si
Abstract : Due to water shortage, municipal reclaimed water rather than surface water was replenished into recycling cooling water system in power plants in some cities in China. In order to understand the effects of the measure on carbon steel corrosion, characteristics of two kinds of foulant produced in different systems were studied in the paper. Differences between municipal reclaimed water and surface water were analyzed firstly. Then, the weight and the morphology of two kinds of foulant were compared. Moreover, other characteristics including the total number of bacteria, sulfate reducing bacteria, iron bacteria, extracellular polymeric substance (EPS), protein (PN), and polysaccharide (PS) in foulant were analyzed. Based on results, it could be concluded that microbial and corrosive risk would be increased when the system replenished by municipal reclaimed water instead of surface water.